2009
DOI: 10.1021/jp903474v
|View full text |Cite
|
Sign up to set email alerts
|

Are Current Semiempirical Methods Better Than Force Fields? A Study from the Thermodynamics Perspective

Abstract: The semiempirical Hamiltonians MNDO, AM1, PM3, RM1, PDDG/MNDO, PDDG/PM3, and SCC-DFTB, when used as part of a hybrid QM/MM scheme for the simulation of biological molecules, were compared on their abilities to reproduce experimental ensemble averages at or near room temperatures for the model system alanine dipeptide in water. Free energy surfaces in the (φ, ψ) dihedral angle space, 3 J(H N ,H R ) NMR dipolar coupling constants, basin populations, and peptide-water radial distribution functions (RDF) were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 108 publications
0
17
0
1
Order By: Relevance
“…3234 The performance of the ff99SB force field has been shown to satisfactorily model hydrogen bonding, outperforming most semi-empirical QM/MM methods in reproducing some experimental properties such as NMR dipolar coupling constants. 3537 …”
Section: Methodsmentioning
confidence: 99%
“…3234 The performance of the ff99SB force field has been shown to satisfactorily model hydrogen bonding, outperforming most semi-empirical QM/MM methods in reproducing some experimental properties such as NMR dipolar coupling constants. 3537 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, scalar couplings calculated by a Karplus relation are sensitive to which empirical Karplus parameters are used 11a, 11b . It also has been suggested that helical structures are not stable enough in ff99SB 11b, 11c, 14 .…”
Section: Introductionmentioning
confidence: 99%
“…At the first stage, a molecular-mechanical minimization was performed to remove the largest strains in the system. At the second stage, the semi-empirical Hamiltonian RM1, whose efficiency was demonstrated in simulations of biomolecules [49, 50], was used to describe the interactions between the substrate and the catalytic residues His263 and His493 more precisely. The most important interatomic distances in the active site of the starting and optimized Tdp1 models are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%